2010
DOI: 10.1080/17441690903352572
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of childhood infectious diseases in Niono, Mali

Abstract: Common childhood diseases vary seasonally in Mali, much of the Sahel, and other parts of the world, yet patterns for multiple diseases have rarely been simultaneously described for extended periods at single locations. In this retrospective longitudinal (1996-2004) investigation, we studied the seasonality of malaria, acute respiratory infection and diarrhoea time-series in the district of Niono, Sahelian Mali. We extracted and analysed seasonal patterns from each time-series with the Multiplicative Holt-Winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…One of the probable reasons for higher occurrence of URTI in the winter is low humidity and increased dust, which may potentially damage immune barriers and 'carry' pathogens, respectively, further increasing the infection risk. 8,9 It was found that 27% of the total medicines were cough and cold combination and only 5% of the total medicines were prescribed as antibiotics. The results of the study carried out by Das et.…”
Section: Discussionmentioning
confidence: 99%
“…One of the probable reasons for higher occurrence of URTI in the winter is low humidity and increased dust, which may potentially damage immune barriers and 'carry' pathogens, respectively, further increasing the infection risk. 8,9 It was found that 27% of the total medicines were cough and cold combination and only 5% of the total medicines were prescribed as antibiotics. The results of the study carried out by Das et.…”
Section: Discussionmentioning
confidence: 99%
“…In a study following community health centres in two towns in the central Mopti region, presumptive malaria accounted for 33.8% (N ¼ 10,123) of all recorded consultation diagnoses between (Rose-Wood et al, 2010. The effects are particularly severe in Sahelian zones like Koulikoro, where the annual rainy season is accompanied by 6 months of high malaria transmission from June to November (Findley et al, 2010). The effects are particularly severe in Sahelian zones like Koulikoro, where the annual rainy season is accompanied by 6 months of high malaria transmission from June to November (Findley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, 68% of reported deaths of Malian children under five were attributed to malaria (PMI, 2011). The effects are particularly severe in Sahelian zones like Koulikoro, where the annual rainy season is accompanied by 6 months of high malaria transmission from June to November (Findley et al, 2010). A study mapping West Africa's geographic risk profile for anaemia, to which malaria is a major contributor, identified a large spatial cluster of low mean haemoglobin concentration (<80 g/l) and maximal risk of anaemia (>95%) over an area abutting Koulikoro Region, where the risk was nearly as high (Soares Magalhães & Clements, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, 68% of reported deaths of Malian children under 5 were attributed to malaria [2]. The effects are particularly severe in Koulikoro and other Sahelian zones, where the rainy season brings six months of high malaria transmission from June to November [3]. A study mapping West Africa’s geographic risk profile for anaemia, to which malaria is a major contributor, identified a large spatial cluster of maximal risk of anaemia (>95%) over an area abutting Koulikoro region, where the risk was nearly as high [4].…”
Section: Introductionmentioning
confidence: 99%